HUBUNGAN FAKTOR SOSIAL EKONOMI PETANI PADI DENGAN PELAKSANAAN PENERAPAN PENGELOLAAN TANAMAN TERPADU (PTT) DI KELURAHAN GALUNG KECAMATAN TAPALANG KABUPATEN MAMUJU - Damayanti, Dani; Irmayani, Irmayani; Darmawan (Jurnal Saintifik (Multi Science Journal), 2023)
Combine Harvester is a rice harvester that can cut standing rice grains, thresh and clean grain while walking in the field. The aims of this study were: 1) To find out what factors influence the use of Combine Harvester in Padangloang Village, Dua Pitue District, Sidenreng Rappang Regency, 2) To determine the efficiency of paddy rice farming in Padangloang Village, Dua Pitue District, Sidenreng Rappang Regency. This study uses a descriptive technique method, namely analysis used to reveal or describe something about a situation that is in accordance with accurate facts from the place under study. There were 52 samples, namely farmers who used the Combine Harvester and were processed using SPSS 26. From the results of the study, it was obtained: The variables of harvesting age, harvest duration, land area and labor partially have a significant influence on rice production. As well as the variables of harvest age, harvest duration, land area and labor simultaneously have an influence on rice production in Padangloang Village, Sidenreng Rappangdan Regency. of 1.73. So that from the three results of data processing efficiency it can be concluded that technical, price and economic efficiency are categorized as efficient because they are equal to 1 which means the Alsintan Combine Harvester System in the harvesting process in Padangloang Village, Dua Pitue District, Sidenreng Rappang Regency is efficient to use.